Performance analysis of biofuel fired trigeneration systems with energy storage for remote households. (15th January 2017) - Huang, Y.; Wang, Y.D.; Chen, Haisheng; Zhang, Xinjing; Mondol, J.; Shah, N.; Hewitt, N.J.
Graphical abstract: Highlights: Techno-economic modelling of biofuel fired trigeneration systems is carried out. Electricity and heat demand profiles in the selected houses are investigated. To adapt the dynamic energy demand an energy storage system is integrated. Load factors and feedstock costs have a considerable impact on the electricity price. Economic performance is influenced by the renewable energy incentive schemes. Abstract: Technical and economic modelling and performance analysis of biofuel fired trigeneration systems equipped with energy storage for remote households were carried out. To adapt the dynamic energy demand for electricity, heating and cooling, both electrical and thermal energy storage devices were integrated to balance larger load changes. The proposed systems were modelled and simulated by using the ECLIPSE process simulation package. Based on the results achieved, technical performance and emissions from the system had been examined. The impact of electrical and thermal energy storages was also investigated. Finally, an economic evaluation of the systems was performed. It was found that for a household, the internal combustion (IC) engine based trigeneration/combined heat and power (CHP) system is more suitable for heat to electricity ratio value below 1.5 and the biomass boiler and Stirling engine based system is beneficial for heat to electricity energy demand ratio lying between 3 and 3.4. Techno-economic analysis of the modelled trigeneration systems showed efficiencies of around 64–70% and Break-even Electricity Selling Prices of around £313/MW h to £357/MW h when fired by biofuels. Results also indicated that the economic viability of this type of trigeneration systems is significantly improved by the Renewable Heat Incentive (RHI) and Feed-In Tariffs schemes (FITs) by up to 46%.